2019
DOI: 10.1364/boe.10.004551
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon microperimetry: sensitivity of human photoreceptors to infrared light

Abstract: Microperimetry is a subjective ophthalmologic test used to assess retinal function at various specific and focal locations of the visual field. Historically, visible light has been described as ranging from 400 to 720 nm. However, we previously demonstrated that infra-red light can initiate visual transduction in rod photoreceptors by a mechanism of two-photon absorption by visual pigments. Here we introduce a newly designed and constructed two-photon microperimeter. We provide for the first time evidence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 35 publications
3
52
0
1
Order By: Relevance
“…Although this study was not specifically designed to ascertain the spectral sensitivity of the photoreceptor mechanisms mediating IR vision, the perception of a 1045-nm pulsed laser beam as green, suggests M-and L-cone activation. 7,15,20,21 Furthermore, recent publications confirm that both cones and rods play a role in this process. Spectrally sensitive measurements in wild type and rod transducing-α-subunit knockout, Gnat1-/-, mouse photoreceptors, and in primate L-and M-cones demonstrated that mammalian cones and rods can be activated by IR light by a twophoton excitation.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Although this study was not specifically designed to ascertain the spectral sensitivity of the photoreceptor mechanisms mediating IR vision, the perception of a 1045-nm pulsed laser beam as green, suggests M-and L-cone activation. 7,15,20,21 Furthermore, recent publications confirm that both cones and rods play a role in this process. Spectrally sensitive measurements in wild type and rod transducing-α-subunit knockout, Gnat1-/-, mouse photoreceptors, and in primate L-and M-cones demonstrated that mammalian cones and rods can be activated by IR light by a twophoton excitation.…”
Section: Discussionmentioning
confidence: 94%
“…In Figure 3, we also observed that sensitivity increases beyond the fovea, which is consistent with the results by Rumiński et al who reported a steep increase in macular sensitivity as the stimulus moved from the center to 4°. 15 In that study, however, measurements beyond 5°eccentricity were not performed. Although publications on one-photon rod-mediated vision revealed a gradual increase of sensitivity with eccentricity, [22][23][24] we found that the differences between parafoveal responses were not statistically significant.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations